Kinetic energy based output power smoothing control and parameters design for PMSG-WECSs. (October 2021) - Zhu, Ying; Guo, Yahui; Wang, Zhicong; Wei, Zhinong
Highlights: The low-pass filter is adopted to replace the traditional average value calculation module in the power smoothing strategy. The parameters of the proposed strategy are designed through the stability analysis of control transfer functions. The overshoot of rotor speed is reduced by choosing the appropriate parameters. Experimental results are not given in all the exsiting kinetic energy based literatures. In this paper, the effectiveness is validated forcefully by experimental results based on a low-power platform. Abstract: The fluctuating output power of wind turbines can lead to the instability of grid, and the effective and economic power smoothing control strategies are essential. Hence, this paper proposes a kinetic energy based power smoothing control strategy for the permanent magnet synchronous generator based wind energy conversion system (PMSG-WECS). The low-pass filter is adopted to replace the traditional average value calculation module. Moreover, the parameters of the proposed power smoothing strategy are designed through the stability analysis of the control transfer functions. The simulation model of a 2MW PMSG-WECS is developed in Matlab/Simulink to validate the feasibility and effectiveness of the proposed power smoothing method. Furthermore, experiments are carried out based on a low power 5.5 kW experimental platform in the lab. Both the simulation and experimental results show that the proposed strategy can provide a satisfactory performance of power smoothing.